HUBUNGAN GAYA BELAJAR TERHADAP NILAI TUTORIAL (Problem Based Learning) MAHASISWA PSKPS FKIK ULM ANGKATAN 2020 - Lucky, Army Gustina Rena; Nurikhwan, Pandji Winata; Husin, Gt. Muhammad Irhamna (Homeostasis, 2024)
Abstract: Learning style is a combination of various ways a person learns to obtain, organize and process the knowledge and information they obtain. Students must know the right learning style so that the learning process can be optimal and get the best results. The aim of the research is to analyze the correlation of learning styles with students' tutorial grades. This research uses analytical observation methods and a cross sectional design. The sample was selected using a total sampling technique. Data collection techniques include filling out The VARK Questionnaire and PBL’s score Complaints Block Relating to the Musculoskeletal System. The results showed that of the 152 samples, learning styles were unimodal (30.3%) and multimodal (69.7%). The average value of unimodal tutorials was 81.67 ± 1.19, while multimodal was 81.42 ± 1.30. The highest value is 83.88, while the lowest value is 77. Based on the Mann-Whitney test, the p-value results are 0.383>0.05, so it can be concluded that there is no difference in learning style and PBL. Keywords: learning style, VARK, Problem Based Learning Abstrak: Gaya belajar merupakan gabungan dari berbagai cara belajar seseorang untuk mendapatkan, mengatur, dan memproses pengetahuan dan informasi yang didapatkannya. Gaya belajar yang tepat harus diketahui oleh mahasiswa agar proses belajar dapat optimal dan mendapat hasil terbaik. Tujuan penelitian adalah menganalisis korelasi gaya belajar terhadap nilai tutorial mahasiswa. Penelitian ini menggunakan metode analitik obervasi dan desain cross sectional. Sampel dipilih melalui teknik total sampling. Teknik pengumpulan data melalui pengisian The VARK Questionnaire dan data nilai tutorial (PBL) Blok Keluhan Berkaitan dengan Sistem Muskuloskeletal. Hasil penelitian menunjukkan bahwa dari 152 sampel, gaya belajar unimodal (30,3%) dan multimodal (69,7%). Rata-rata nilai tutorial unimodal 81,67±1,19, sedangkan multimodal 81,42±1,30. Nilai tertinggi adalah 83,88, sementara nilai terendah 77. Berdasarkan uji Mann-Whitney menunjukkan hasil p-value 0,383>0,05, sehingga disimpulkan tidak ada perbedaan gaya belajar terhadap nilai tutorial (Problem Based Learning). Kata-kata kunci: gaya belajar, VARK, Problem Based Learning, tutorial